Trilha de sons do Liceu: o estudo da paisagem sonora e os desafios da educação musical na escola pública - FERREIRA, Elma Vilma Silva (2020)
With the increasing urbanization of cities, high levels of noisy pollution have been felt, and it is affecting different aspects of human relationships, including the teaching and the learning in schools. The goal was to find out if a study of the sound scenario of a public institution can contribute to the perception of the influence of acoustic environment characteristics attached to the level of attention of students during classes, focusing on the historical path of music education in Brazil, the knowledge about sound landscape, acoustic ecology and pedagogical perspectives in sound education. Through the study carried out at the Centro de Ensino Liceu Maranhense which was based on the use of qualitative methodology, it was verified participant observation and it was applied questionnaires with students, teachers, coordination and direction, as well as the development of investigative and attentive hearing activities and it was conducted measurement circuits in different school spaces. The study found that the school's soundscape is composed of varied and intense noises that were noticed and recorded by students; it was observed that the sound pressure levels measured in the classroom are above the recommended in official documents; it was found that most professionals classified the school acoustic environment as soundly polluted. It is concluded that the conditions of the school acoustic environment compromise the attention, the communication and, therefore, the learning of the students, but that the reality can be transformed, especially if the initiatives of musical and sound education - which were developed during the investigation – become part of daily routine of school and also contribute to the training of potential learners, able to collaborate for the rebuilt of healthier soundscapes.